2014
DOI: 10.3390/ijms15010712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the rs10046 Polymorphism of Aromatase (CYP19) in Premenopausal Onset of Human Breast Cancer

Abstract: The CYP19 gene encodes aromatase, an enzyme catalyzing the conversion of androgens to estrogens. Studies analyzing associations between single nucleotide polymorphisms in CYP19 and breast cancer risk have shown inconsistent results. The rs10046 polymorphism is located in the 3′ untranslated region of the CYP19 gene, but the influence of this polymorphism on breast cancer risk is unclear. In this study, we investigated the impact of rs10046 SNP on breast cancer risk, age at onset and association with clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Association analysis between rs10046 and BC in different populations showed inconsistent results (Zhang et al, 2009;Pineda et al, 2013). Karin et al (Zins et al, 2014) reported that the TT genotype of this polymorphism was associated with an increased BC risk. Our data contradicted two earlier studies in which the CC genotype had a reduced risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Association analysis between rs10046 and BC in different populations showed inconsistent results (Zhang et al, 2009;Pineda et al, 2013). Karin et al (Zins et al, 2014) reported that the TT genotype of this polymorphism was associated with an increased BC risk. Our data contradicted two earlier studies in which the CC genotype had a reduced risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…For rs743,572 polymorphism of the CYP17gene, significant association was found with breast cancer risk in Canadian and Russian populations (Artamonov et al, 2003;Cribb et al, 2011), but in a study on Chinese population, no evidence of association was observed (Han et al, 2005). The rs10,046 polymorphism of the CYP19gene has been also shown inconsistent results, so that no significant association was found in USA and China (Haiman et al, 2002;Zhang et al, 2009), but recent studies in Austria and Xinjiang Uigur found significant differences in distribution of alleles and genotypes between women with breast cancer and normal women (Zins et al, 2014;Yang et al, 2015). Finally, the rs4646903 polymorphism of the CYP1A1 gene can also found to be investigated in several studies and different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Tuy nhiên, nghiên cứu của Kristensen và cs (2000) ở phụ nữ Na Uy, kết luận rằng phụ nữ có alen C tại SNP rs10046 có nguy cơ mắc ung thư vú giảm so với phụ nữ có alen T [6]. Nghiên cứu của Zins và cs gần đây, kiểu gen TT được cho là làm tăng nguy cơ mắc ung thư vú ở phụ nữ tuổi dưới 50, nhưng không làm tăng nguy cơ mắc ở nhóm bệnh nhân tuổi trên 50 [14]. Các nghiên cứu của Ghisari và cs (2014) ở phụ nữ bản địa (sinh sống tại vùng Bắc cực) [15], Ralp và cs (2007) ở Mĩ [16], Dunning và cs (2004) [4] ở phụ nữ Bồ Đào Nha, đều kết luận SNP rs10046 của gen CYP19A1 không có ảnh hưởng nào đến nguy cơ mắc ung thư vú ở phụ nữ.…”
Section: Thảo Luậnunclassified